2013
DOI: 10.1586/14760584.2014.863715
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress concerning CpG DNA and its use as a vaccine adjuvant

Abstract: CpG Oligonucleotides (ODN) are immunomodulatory synthetic oligonucleotides designed to specifically agonize Toll-like receptor 9. Here, we review recent progress in understanding the mechanism of action of CpG ODN and provide an overview of human clinical trial results using CpG ODN to improve the vaccines for cancer, allergy and infectious disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(145 citation statements)
references
References 159 publications
2
138
0
Order By: Relevance
“…What we know now is that TLR9 binding is influenced partly by specific base sequences, as well as the sugar phosphate backbone, conjugation to the antigen and dose of the antigen, as well as administration route and schedule 21) 28) 42) 44)-47) . These highlight considerations on careful formulation and evaluation of the antigen with CpG ODN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What we know now is that TLR9 binding is influenced partly by specific base sequences, as well as the sugar phosphate backbone, conjugation to the antigen and dose of the antigen, as well as administration route and schedule 21) 28) 42) 44)-47) . These highlight considerations on careful formulation and evaluation of the antigen with CpG ODN.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these immunostimulatory properties have been tapped for a range of non-antigen specific therapy of allergens and cancers; as well as antigen-specific generation of B and T cell immune responses to synthetic peptide-and recombinant protein-based vaccines 21) . Besides antibodies which are crucial for parasite clearance in the latter stages of infection, several studies have shown that the control of malaria is partially dependent on the generation of Th1-type immunity 32) .…”
Section: Immunostimulatory Dna Sequencesmentioning
confidence: 99%
“…The ability of NP-cdGMP to adjuvant immune responses in trans to particulate antigen provides flexibility for vaccine production and facilitates inclusion of NP-cdGMP into existing vaccine platforms. Although many danger signals are effective in promoting immune responses in mice, type I IFN-inducing adjuvants have shown particular promise in nonhuman primate models (87,88) and humans (89,90) for promoting superior cellular and humoral immunity. The nanoparticle delivery strategy demonstrated here provides a simple means to promote both the safety and efficacy of CDNs as a novel type I IFN-promoting adjuvant, with potential relevance to human vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] More than 600 preclinical studies investigating the treatment or prevention of cancers, infections, and allergies with CpG ODNs have been implemented to date, 8 and more than 100 clinical trials have either been completed or are currently in progress. 9 Many of the CpG ODNs developed to date have been single-stranded synthetic ODNs with ~20 bases, and they are divided broadly into four classes depending upon the differences in their structure and immunoreactivity. Of these four classes, almost all the CpG ODNs used in clinical trials have been class-B CpG (CpG-B) ODNs (also known as K-type ODNs), whereas class-A CpG (CpG-A) ODNs (also known as D-type ODNs) have also been used but in fewer clinical trials.…”
Section: Introductionmentioning
confidence: 99%